Parental Satisfaction Metrics in Paediatric Day-Care Surgical Environment - Ubaid Ullah,; Fatima, Batool; Maryam,; Janjua, Azwa; Aman, Nadir; Bashir, Kashif (Indus Journal of Bioscience Research, 2025)
Introduction: Pediatric day-care surgery has benefits like shorter hospital stays, cost savings, and quicker recovery. Understanding parental satisfaction, especially in resource-limited settings, is crucial for healthcare quality. This study analyzes factors affecting satisfaction in pediatric day-care surgery services. Methodology: A cross-sectional study at Mayo Hospital’s Paediatric Surgery Department in Lahore involved 163 parents of children aged 1-12 undergoing day-care surgery. Satisfaction was evaluated with the COPS-D (13) questionnaire, covering eight dimensions. SPSS version 20 was used for data analysis, applying chi-square tests to explore links between parental satisfaction and socio-demographic factors (p ≤ 0.05). Results: The average parental satisfaction was 75.76 ± 15.63%. Most parents (71.8%) were highly satisfied, while 24.5% were moderately satisfied and 3.7% were dissatisfied. Satisfaction wasn't significantly linked to gender (p = 0.609), child's age (p = 0.734), diagnosis (p = 0.588), socio-economic status (p = 0.688), or occupation (p = 0.354). Yet, parental age (p = 0.071) and education level (p = 0.114) hinted that older and less-educated parents reported higher satisfaction. Conclusion: Parental satisfaction in paediatric day-care surgery was high (70% positive). Trends hint education level and parental age might affect satisfaction. Optimal patient-centered care is crucial for enhancing parental experiences in paediatric surgical settings.